A Dinuclear Gold(I) Bis(Carbene) Complex Based on a Ditopic Cyclic (Aryl)(Amino)Carbene Framework. Issue 22 (15th November 2016) - Deck, Eva; Reiter, Kevin; Klopper, Wim; Breher, Frank
Abstract : A dinuclear gold(I) bis(carbene) complex based on a 1, 5‐dihydropyrazolo[3, 4‐ f ]indazoline‐3, 7‐diylidene ligand framework is reported. The bridging bis(carbene) ligand is the first example of a ditopic cyclic (aryl)(amino)carbene (CArAC). The ligand precursor 2, 6‐diethyl‐1, 5‐diphenyl‐1, 5‐dihydropyrazolo[3, 4‐ f ]indazole‐2, 6‐diium (2H2 ) is readily available from the literature‐known starting material 1, 5‐diphenyl‐1, 5‐dihydropyrazolo[3, 4‐ f ]indazole (1 ) and two equivalents of the Meerwein salt [Et3 O][BF4 ]. The NHC gold(I) hydroxide complex [IPrAuOH] proved to be a valuable precursor for the synthesis of the dinuclear gold complex [(IPr)2 Au2 (μ‐2 )][BF4 ]2 (3 ) [IPr = 1, 3‐bis(2, 6‐diisopropylphenyl)imidazole‐2‐ylidene]. The compounds under study were fully characterized by various methods, also including X‐ray crystallographic studies on single crystals of2H2 and3 . The ligand was developed in order to explore a possibly enhanced mediation of electronic metal‐to‐metal communication via the π‐system. Density functional theory calculations revealed, however, that the electronic communication in the parent system, or in other ring‐substituted derivatives, is only small and predominantly mediated by the σ‐bond framework. The calculations also predict that the introduction of an additional donor functionality to the central arene ring of the ditopic bis(carbene), which is able to act as bridging entity and forms an additional metal‐ligand bond, increases the communication between the two central metal atoms. The amount of electronic communication in the bis(carbene) complexes under study appears to be a direct function of the number of metal‐ligand contacts. Abstract :